2021
DOI: 10.30901/2227-8834-2021-2-53-62
|View full text |Cite
|
Sign up to set email alerts
|

Comparative analysis of the chemical composition and size of starch granules in grain between diploid and tetraploid sweetcorn cultivars

Abstract: Background. Improving the taste and nutritional value of sweetcorn using genetic selection techniques is an important trend. The tetraploid sugary maize cultivar ‘Baksanskaya sakharnaya’ (k-23426) has a number of advantages in terms of taste and marketability over traditional diploid varieties.The purpose of the research was to identify the distinctive biochemical characteristics that affect the taste of this cultivar in comparison with the diploid reference (cv. ‘Rannyaya Lakomka’, с-1775).Materials and metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Accordingly, the number of dominant alleles of the Su2 gene (wild type) in ordinary corn will affect the synthesis of normal starch in the same proportions as Su2Su2Su2 (2n) Su2Su2Su2Su2Su2Su2 (4n) without the accumulation of sugar in the maize grain. The findings of investigations into the grain chemical components affecting the taste qualities of tetraploid and diploid sweet maize have shown that an increase in the number of genes is accompanied by a change in the quantitative, rather than qualitative, biochemical profile characteristics [31]. Studies of the effect of different genome ploidy of waxy or amylose maize on starch properties have not been found in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…Accordingly, the number of dominant alleles of the Su2 gene (wild type) in ordinary corn will affect the synthesis of normal starch in the same proportions as Su2Su2Su2 (2n) Su2Su2Su2Su2Su2Su2 (4n) without the accumulation of sugar in the maize grain. The findings of investigations into the grain chemical components affecting the taste qualities of tetraploid and diploid sweet maize have shown that an increase in the number of genes is accompanied by a change in the quantitative, rather than qualitative, biochemical profile characteristics [31]. Studies of the effect of different genome ploidy of waxy or amylose maize on starch properties have not been found in the literature.…”
Section: Introductionmentioning
confidence: 99%